2023
DOI: 10.1186/s12944-023-01777-4
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine chemerin overexpression in trophoblasts leads to dyslipidemia in pregnant mice: implications for preeclampsia

Abstract: Background The adipokine chemerin regulates adipogenesis and the metabolic function of both adipocytes and liver. Chemerin is elevated in preeclamptic women, and overexpression of chemerin in placental trophoblasts induces preeclampsia-like symptoms in mice. Preeclampsia is known to be accompanied by dyslipidemia, albeit via unknown mechanisms. Here, we hypothesized that chemerin might be a contributor to dyslipidemia. Methods Serum lipid fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Both LDLR and chemerin expression rely on the transcription factor SREBP2. 9,50 We observed that preeclamptic explants contained more SREBP2 and less LDLR at the protein level. Theoretically, this might shift the balance in favor of chemerin.…”
Section: Discussionmentioning
confidence: 77%
“…Both LDLR and chemerin expression rely on the transcription factor SREBP2. 9,50 We observed that preeclamptic explants contained more SREBP2 and less LDLR at the protein level. Theoretically, this might shift the balance in favor of chemerin.…”
Section: Discussionmentioning
confidence: 77%
“…The disturbed sFlt-1/VEGFa ratio involves the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) pathway. Finally, extracellular signal-regulated kinase 1/2 (ERK1/2) upregulation might lead to lipid accumulation.Figure4summarizes the findings from references[110,158]. CMKLR1, chemerin-like receptor 1; CCRL2, CC motif chemokine receptor-like 2.…”
mentioning
confidence: 80%
“…Additionally, chemerin levels were low in subfertile males, most likely due to their elevated luteinizing hormone levels [172], and this was suggested to reflect a link between chemerin and reproductive function. 4 summarizes the findings from references [110,158]. CMKLR1, chemerin-like receptor 1; CCRL2, CC motif chemokine receptor-like 2.…”
Section: Sex Differencesmentioning
confidence: 99%
“…In a recently published study, Tan et al demonstrated in a mouse model that placental chemerin overexpression elevated maternal serum lipid level, leading to lipid accumulation in the placenta. Chemerin overexpression in this study was associated with increased levels of phospholipids, lysophospholipids, and cholesterol in both maternal blood and the placenta [ 111 ]. Lipid oxidation products (e.g., oxLDL) cause oxidative stress, endothelial dysfunction, and acute atherosclerosis [ 47 , 51 ].…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%
“…That leads to the enhanced release of lipids and lipid-related proteins (triglycerides, cholesterol, phospholipids, and chemerin) from the placenta into the maternal circulation. On the other hand, chemerin causes also a lower LDL uptake from the circulation to the placenta, and this contributes to dyslipidemia in the patient [ 111 ]. Gu et al investigated the impact of chemerin overexpression on endothelial function, arterial stiffness, and early atherosclerosis in patients with hypertension and presented that a high chemerin serum level was an independent predictor of impaired endothelial function and increased arterial stiffness, even after adjustment for metabolic variables, inflammatory markers, and adipokines [ 112 ].…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%